A supramolecular diagnosis and treatment integrated agent: Synthesis and self-assembly of stimulus-responsive star-shaped copolymer. (5th July 2020) - Zhou, Mi; Ling, Feng; Li, Jie
Graphical abstract: Highlights: A four-arms supramolecular copolymer with temperature-response and dis-assembly. The copolymer chelated with Gd 3+ ion exhibit T1 relaxivity and can be disassembled. The copolymer micelles display burst and thermal-response drug delivery. Abstract: We now report a star-shaped supramolecular copolymer for diagnosis and treatment by chelated with Gd 3+ ion as magnetic resonance imaging (MRI) contrast agent and drug-carried for controlling release agent. The copolymer is prepared by the host-guest inclusion complexation between the host polymer polycaprolactone-β-cyclodextrin (4sPCL-CD) and the guest polymer adamantylamine-poly-L-lactic-block-poly(N-isopropylacrylamide-co-2-hydroxyethylmethacrylate-diethylenetriamine penta acetic acid) (AD-PLLA- b -P(NIPAM- co -HEMA-DTPA)) and can self-assemble into spherical micelles in aqueous solution. By adding 2-adamantylamine hydrochloride (AD-NH2 ), the supramolecular copolymer can be disassembled to the host and guest polymers and its molecular weight will be decreased. When the polymeric micelles are chelated with Gd 3+ ion, they exhibit T1 relaxivity as a kind of contrast agent for MRI. This contrast agent can maintain a large molecular size to stay in vivo and also can reduce its molecular size quickly and metabolize rapidly from the body by disassembled. Also, as the copolymer carries drugs, it displays burst release and thermal-response release behaviors, due to its dis-assembly and thermal-response PNIPAM chain respectively. Thus, the supramolecular copolymer from the host-guest inclusion complexation is expected to realize diagnosis and treatment feature for clinic.